2019
DOI: 10.1136/bmjopen-2018-027633
|View full text |Cite
|
Sign up to set email alerts
|

Identifying relationships between sleep posture and non-specific spinal symptoms in adults: A scoping review

Abstract: ObjectivesThe objectives of this scoping review were to identify (1) study designs and participant populations, (2) types of specific methodology and (3) common results, conclusions and recommendations from the body of evidence regarding our research question; is there a relationship between sleep posture and spinal symptoms.DesignScoping review.Data sourcesPEDro, Embase, Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, Medline, ProQuest, PsycINFO, SportDISCUS and grey literature fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…Sleep posture was not explored in either study. Further, the lack of research focus on spinal symptoms associated with sleep posture was highlighted in a recent scoping review, in which only four studies were found to address these topics [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep posture was not explored in either study. Further, the lack of research focus on spinal symptoms associated with sleep posture was highlighted in a recent scoping review, in which only four studies were found to address these topics [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sleep-associated musculoskeletal disorders and pain can manifest as significant consequences of sleep complaints and deprivation. Sleep posture itself cannot indicate whether the posture is poor or problematic, although this risk factor is modifiable and can be mitigated by using the proper mattress and pillows or engaging in physical exercise [ 12 , 47 , 48 ]. We are aiming for a machine learning-based measurement of spinal alignment and limb placement with a classification of sleeping postures that could be important in identifying related problems such as neck and back pain [ 12 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from sleep quality, sleep posture constitutes another important category in the field [ 8 ]. Different lying or recumbent positions in sleep alters spinal loading, intervertebral disc pressure, and muscle activity [ 9 , 10 ], potentially leading to sleep-related musculoskeletal pain and disorders such as neck spasm, back pain and waking symptoms [ 11 , 12 ]. For example, a prolonged non-symmetrical sleeping posture might lead to structural spinal changes and symptoms [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations